1986
DOI: 10.1002/1097-0142(19860315)57:6<1145::aid-cncr2820570615>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin production by malignant thyroid tumors. An immunocytochemical and radioimmunoassay study

Abstract: Four hundred thirty surgical and biopsy specimens of malignant thyroid tumors of 323 patients were analyzed by histologic and immunocytochemical examination for their thyroglobulin (TG) content. Almost 95% of the differentiated thyroid carcinomas of follicular origin contained immunoreactive TG. The authors could not demonstrate TG in anaplastic carcinomas. Postoperative follow-up and serum TG determinations were available for 111 athyroid patients. Serum TG was elevated in five patients with metastatic or rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Thyroglobulin is an excellent marker of papillary and follicular carcinomas but is a poor marker of anaplastic thyroid carcinomas and, as might be expected, is not a marker of medullary (neuroendocrine) carcinomas of the thyroid. 163 TTF-1.-Importantly, TTF-1 is an even more-sensitive marker of thyroid carcinomas than thyroglobulin is and is expressed in more than 90% of thyroid carcinomas, with the solitary exception of the anaplastic variant, in which the sensitivity is close to zero. In addition, TTF-1 can be employed as a marker of neuroendocrine carcinomas of the thyroid, such as medullary carcinomas.…”
Section: Thyroid Markersmentioning
confidence: 99%
“…Thyroglobulin is an excellent marker of papillary and follicular carcinomas but is a poor marker of anaplastic thyroid carcinomas and, as might be expected, is not a marker of medullary (neuroendocrine) carcinomas of the thyroid. 163 TTF-1.-Importantly, TTF-1 is an even more-sensitive marker of thyroid carcinomas than thyroglobulin is and is expressed in more than 90% of thyroid carcinomas, with the solitary exception of the anaplastic variant, in which the sensitivity is close to zero. In addition, TTF-1 can be employed as a marker of neuroendocrine carcinomas of the thyroid, such as medullary carcinomas.…”
Section: Thyroid Markersmentioning
confidence: 99%
“…An alternative to periodic radioiodine scans to search for metastatic disease in patients who have undergone total thyroidectomy is serum thyroglobulin (Tg) assay [124,125]. Almost all differentiated thyroid cancers contain immunoreactive Tg, but anaplastic thyroid cancers do not.…”
Section: Thyroid Carcinomamentioning
confidence: 99%
“…Thyroglobulin expression assessed by immunohistochemistry has been used for its diagnostic value in differentiating thyroid cancer tissue for decades [ 29 , 30 ]. Dralle et al reported no difference in radioiodine uptake positivity in recurrent lesions with or without Tg staining; however, they used less sensitive techniques for radioactivity quantification than in the current work [ 31 ].…”
Section: Discussionmentioning
confidence: 99%